Experiential Tourism in the Peruvian Andes: A Cultural View - Barbieri, Carla (2016)
Community-based experiential tourism has been developed to: a) Foster rural development, b) Expand the benefits of major tourism attractions. Government & NGOs provide technical assistance & training. The Problems: 1) Its impacts in the Andes is anecdotal & contradictory. 2) Indigenous communities are extremely vulnerable to outside influences.